Trije modeli 'upesnjene zgodovine' v poeziji Konstantina Kavafisa - Fabjan Andritsakos, Dragica (Keria (Ljubljana), 2009)
The introductory part of the article shows Cavafy's model of setting history to poetry as a collection of well-known, less known, or completely fictional figures. The main part presents four poems translated into Slovene, accompanied by a literary-critical analysis and illustrated with more of Cavafy's poetry in translation. The subsequent synthesis of the four texts reveals Cavafy's method of placing each character in a historical environment:providing a sketch rather than a full portrayal, he tinges it withan illusion of history.
Keywords: grška književnost; grška poezija; Kavafis, Konstantinos Petrou; literarne študije; literarni motivi